Characterization of the juvenile koala gut microbiome across wild populations. (12th January 2022) - Blyton, Michaela D. J.; Soo, Rochelle M.; Hugenholtz, Philip; Moore, Ben D.
Summary: In this study we compared the faecal microbiomes of wild joey koalas ( Phascolarctos cinereus ) to those of adults, including their mothers, to establish whether gut microbiome maturation and inheritance in the wild is comparable to that seen in captivity. Our findings suggest that joey koala microbiomes slowly shift towards an adult assemblage between 6 and 12 months of age, as the microbiomes of 9‐month‐old joeys were more similar to those of adults than those of 7‐month‐olds, but still distinct. At the phylum level, differences between joeys and adults were broadly consistent with those in captivity, with Firmicutes increasing in relative abundance over the joeys' development and Proteobacteria decreasing. Of the fibre‐degrading genes that increased in abundance over the development of captive joeys, those involved in hemicellulose and cellulose degradation, but not pectin degradation, were also generally found in higher abundance in adult wild koalas compared to 7‐month‐olds. Greater maternal inheritance of the faecal microbiome was seen in wild than in captive koalas, presumably due to the more solitary nature of wild koalas. This strong maternal inheritance of the gut microbiome could contribute to the development of localized differences in microbiome composition, population health and diet through spatial clustering of relatives.